STUDI HIDROGEOFISIKA DAERAH PANAS BUMI NON-VULKANIK LAINEA KABUPATEN KONAWE SELATAN MENGGUNAKAN METODE GEOLISTRIK TAHANAN JENIS - Syamsul R Haraty (Jurnal Rekayasa Geofisika Indonesia, 2022)
Research has been carried out in the non-volcanic geothermal area of Lainea, South Konawe Regency on hydrogeophysics using the geoelectrical method of resistivity. The purpose of this study was to determine the subsurface lithology and hydrological potential in the research area. Geoelectrical resistivity measurements were carried out on 5 measurement lines using the Schlumberger configuration and data processing using the PROGRESS application. The results of the alignment between the subsurface model, resistivity table and geological conditions, the lithology of the research area consists of overburden with resistivity values between 18.09 ohmmeter - 241.2 ohmmeter, sandstone with resistivity value 19.81 Ohmmeter - 344.6 Ohmmeter and clay with a resistivity value of 2.88 Ohmmeter – 12.78 Ohmmeter and the potential of the aquifer is in sandstone lithology with different depths and thicknesses between measurement paths.Key words: Geothermal, Lainea, Geoelectrical,lithology,aquifer